Exfoliation Syndrome and Exfoliation Glaucoma in the Navajo Nation - Ayesha Patil; Cole Swiston; Ryan T. Wallace; Chase Paulson; Matthew E. Conley; Lori McCoy; Craig Chaya; Barbara Wirostko (Vision, 2022)
(1) Background: Exfoliation syndrome (XFS) is a common cause of secondary open angle glaucoma. In 1971, Faulkner et al. estimated the prevalence of XFS among 50 Navajo Nation residents as 38%. Given that XFS can cause irreversible blindness secondary to glaucoma (XFG), this study aims to identify the current prevalence of XFS among Navajo Nation residents within the Four Corners region of the U.S. (2) Methods: A retrospective chart review was conducted from 2016 to 2021 for patients aged 18 and older. All patients with XFS or XFG diagnosed by slit lamp exam were identified through chart review. (3) Results: Of the 1152 patient charts available for review, eight patients (11 eyes) were diagnosed with XFS with three patients (4 eyes) demonstrating concomitant XFG. Within this XFS population, 50% of the patients identified as male, with a mean age of 73 years. The overall prevalence of XFS was 0.7% and the overall prevalence of XFG was found to be 0.26%. The rate of XFG among patients with XFS was 37.5%. (4) Conclusion: Compared to Faulkner’s study of Navajo Nation residents in 1971, our findings show a considerably lower prevalence of XFS at 0.7%. We present the largest study to date of XFS among this population.